The effects of different irrigation agents on root canal dentine micro-hardness and surface roughness - Öztekin, Faruk; Adıgüzel, Özkan (My University, 2019)
Aim: Successful endodontic treatments rely on sufficient mechanical preparation and irrigation of the root canal followed by an adequate three-dimensional filling. This study investigated the changes in root dentine micro-hardness and surface roughness upon treatment with different irrigating agents. Methodology: A total of 60 human maxillary incisors and canine teeth were used in this study. The crowns of all teeth were decoronated and roots were divided longitudinally. The samples were separated into three groups prior to irrigation. A 5% NaOCl irrigation agent was applied to the first group, a QMix agent was used for the second group, and a 2% CHX agent was used for the third group. All irrigations were performed for 15 minutes. Following irrigation, microstructural and surface-roughness measurements were taken again from all samples. Results: Micro-hardness was not significantly different between QMix or 5% NaOCl (p>0.05). A significant difference was observed between the QMix- and 2% CHX-treated groups, and between the 5% NaOCl- and QMix-treated groups (p<0.05). A significant difference in surface roughness was observed between the QMix and 2% CHX, and between the 5% NaOCl and QMix (p<0.05). No difference in surface roughness was observed between 5% NaOCl or 2% CHX. The 5% NaOCl and QMix agents reduced the dentine micro-hardness equal to or more than that of the 2% CHX agent. The QMix agent also increased the dentine surface roughness significantly more than the other agents. The 5% NaOCl and 2% CHX agents increased surface roughness equally. Conclusions: It was seen that all of the irrigation agents used in our study affected dentin microhardness and surface roughness at different rates.
Keywords: Diş Hekimliği